2019
DOI: 10.1002/aet2.10427
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Diversity and Inclusion: An Organized Approach Through a Medical Specialty Academy

Abstract: Background: The benefits of a diverse workforce in medicine have been previously described. While the population of the United States has become increasingly diverse, this has not occurred in the physician workforce. In academic medicine, underrepresented in medicine (URiM) faculty are less likely to be promoted or retained in academic institutions. Studies suggest that mentorship and engagement increase the likelihood of development, retention, and promotion. However, it is not clear what form of mentorship c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…Research shows that patientprovider racial or ethnic concordance can improve patient-provider communication and increase patient health care engagement, 94,95 highlighting the importance of ongoing interventions to increase research and medical workforce diversity and the need to increase patientprovider racial or ethnic concordance in genetics care. [96][97][98][99] Additional interventions might include (1) specialized case managers to streamline care and address patient questions, a model that has been successful in the diagnostic pathway, 100 and (2) leveraging celebrity hereditary cancer syndrome diagnosis disclosure, which has correlated with enhanced genetic testing usage and genetics knowledge seeking in the past, to create accessible and relatable interventions aimed at reducing stigma and increasing information access for lower health literacy populations.…”
Section: Discussion: the Future Of Equitable Care Delivery In Hereditary Cancer Syndromesmentioning
confidence: 99%
“…Research shows that patientprovider racial or ethnic concordance can improve patient-provider communication and increase patient health care engagement, 94,95 highlighting the importance of ongoing interventions to increase research and medical workforce diversity and the need to increase patientprovider racial or ethnic concordance in genetics care. [96][97][98][99] Additional interventions might include (1) specialized case managers to streamline care and address patient questions, a model that has been successful in the diagnostic pathway, 100 and (2) leveraging celebrity hereditary cancer syndrome diagnosis disclosure, which has correlated with enhanced genetic testing usage and genetics knowledge seeking in the past, to create accessible and relatable interventions aimed at reducing stigma and increasing information access for lower health literacy populations.…”
Section: Discussion: the Future Of Equitable Care Delivery In Hereditary Cancer Syndromesmentioning
confidence: 99%
“…Most PPs aim to support and facilitate educational and healthcare career advancement for UIM racial and ethnic groups. 1 9 , 27 , 30 , 31 , 35 , 38 , 41 , 47 – 50 , 52 , 56 – 58 , 60 , 66 , 67 Few programs share their participant selection criteria in detail and rarely state race/ethnicity criteria. 30 Commonly, programs used proxy criteria for race/ethnicity including being from educationally/economically disadvantaged backgrounds.…”
Section: Infrastructure and Framework For Implementing Pathway Programsmentioning
confidence: 99%
“… 8 Within emergency medicine (EM), women account for only 25% of physicians, while Black, LatinX, and Native American physicians comprise less than 10% of all active emergency physicians. 9 Furthermore, a recent study projects that EM will take about 54 years to reach the level of LatinX faculty representation commensurate with that of the US population. 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…73 Similarly, a survey of members in the Academy for Diversity and Inclusion in Emergency Medicine within the Society for Academic Emergency Medicine found that participation led to more publications, didactic presentations, grand round presentations, and mentor/mentee relationships. 74 The Association of Black Cardiologists aims to promote diversity, boost collegiality in the field, and promote health disparities research and interventions. Through its scholarships, this group was able to partially fund cardiology subspecialty training for 44 Black cardiologists.…”
Section: Promote National Organization Membershipmentioning
confidence: 99%